Home fertilizer teaching module for Aborigine people - Nor Hasniza Ibrahim; Johari Surif; Norulhuda Ismail; Nur Sahrizan Serman; Mangai Solomon Mahanan; Chuzairy Hanri; Muhammad Khairul Arif Ahamad (Institute of Advanced Engineering and Science, 2022)
The Aborigines of Malaysia portray limited knowledge of domestic wastes conversion into homemade fertilizer for crops which is also needed to facilitate proper home hygiene. Therefore, this study developed a Home fertilizer teaching module that applies 5E model to educate the knowledge deficient Aborigine People. The study used a qualitative research approach through the collection of open-ended data and analyzed based on themes. The research procedure was divided into: i) Development of the Home fertilizer module; and ii) Validation of the Home fertilizer module. Validation of the module was done by eight experts in teaching science and mathematics who were selected based on the purposive sampling technique according to the study aim. An open-ended questionnaire that contains ten items about the suitability of the module to be implemented among the Aborigines community, the content of the module, and involvement of STEM learning was the instrument of the study. Results showed that the content of the module is easy to understand with a clear objective and also stimulates science, technology, engineering, and mathematics (STEM) learning. Also, the module was considered a sanitary STEM module that is suitable for educating the Aborigine people on domestic waste conversion into homemade fertilizer and maintaining a cleaner environment.